Perspektif Ekonomi Islam Terhadap Kerja Sama Ambe’en (Studi Kasus Perahu Sumber Barokah Di Pelabuhan Muncar Kabupaten Banyuwangi) - Amin, Risma; Ummal Khoiriyah; Zainuddin (Lembaga Pusat Penelitian dan Pengabdian kepada Masyarakat (LP2M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2022)
Kerja sama ambe’en is one type of cooperation that relies on the basic values ​​of Islamic economics. It can be cantegorized as syirkah al-Inaan. This study focuses on: the implementation of kerja sama ambe'en and the Islamic economic perspective on kerja sama ambe'en, a case study of Sumber Barokah Boat at Muncar Port, Banyuwangi Regency. The research method used was a qualitative approach. The data collected were primary data and secondary data. Data source obtained through observation, interviews with owners, investors, and the person in charge in Sumber Barokah Boat, as well as documentation. Analysis technique used was domain analysis, taxonomic analysis and theme analysis. Based on the results of the analysis in this study, it shows that kerja sama ambe’en on the Sumber Barokah Boat implements syirkah al-Inaan contract by combining assets or capital. The capital that is given is the form of working capital by the owner of the Sumber Barokah Boat and capital that paid as needed, while the other parts provides capital in 80,000,000 with 10% profit sharing through an agreement. This cooperation has covered almost all the basic values ​​of Islamic economics.